Perception of animate motion in dogs - Abdai, Judit (Frontiers in Psychology, 2025)
Various motion cues can lead to the perception of animacy, including (1) simple motion characteristics such as starting to move from rest, (2) motion patterns of interactions like chasing, or (3) the motion of point-lights representing the joints of a moving biological agent. Due to the relevance of dogs in comparative research and considering the large variability within the species, studying animacy perception in dogs can provide unique information about how selection for specific traits and individual-level (social) differences may shape social perception. Despite these advantages, only a few studies have investigated the phenomenon in dogs. In this mini-review, we discuss the current findings about how specific motion dynamics associated with animacy drive dogs' visual attention.